Metabolic adaptations to weight loss: a brief review - Martínez-Gómez, M. G.; Roberts, B. M. (The Journal of Strength and Conditioning Research, 2022)
As the scientific literature has continuously shown, body mass loss attempts do not always follow a linear fashion nor always go as expected even when the intervention is calculated with precise tools. One of the main reasons why this tends to happen relies on our body's biological drive to regain the body mass we lose to survive. This phenomenon has been referred to as "metabolic adaptation" many times in the literature and plays a very relevant role in the management of obesity and human weight loss. This review will provide insights into some of the theoretical models for the etiology of metabolic adaptation as well as a quick look into the physiological and endocrine mechanisms that underlie it. Nutritional strategies and dietetic tools are thus necessary to confront these so-called adaptations to body mass loss. Among some of these strategies, we can highlight increasing protein needs, opting for high-fiber foods or programming-controlled diet refeeds, and diet breaks over a large body mass loss phase. Outside the nutritional aspects, it might be wise to increase the physical activity and thus the energy flux of an individual when possible to maintain diet-induced body mass loss in the long term. This review will examine these protocols and their viability in the context of adherence and sustainability for the individual toward successful body mass loss.